A PRELIMINARY STUDY OF METHANE INCLUSIONS IN ALKALINE IGNEOUS ROCKS OF THE KOLA IGNEOUS PROVINCE, RUSSIA: IMPLICATIONS FOR THE ORIGIN OF METHANE IN IGNEOUS ROCKS - Potter J.; Rankin A.H.; Treloar P.J.; Ting W.; Ni P.; Nivin V.A. (My University, 1998)
Fluid inclusions from the Kovdor, Khibina and Lovozero complexes of the Kola alkaline igneous province have been investigated using microthermometric techniques and PVTX modelling. CH4 inclusions, found in all three complexes, are always secondary in origin and frequently occur in curvilinear arrays associated with secondary H2O-dominant inclusions and, in Khibina, CH4-H2O inclusions. The secondary nature of the CH4-bearing inclusions appears to preclude a direct magmatic origin for the methane, which is supported by preliminary C-isotope data which indicate an abiogenic origin. Isochore projections for primary CO2- and H2O-dominant inclusions intersect the volatile-saturated, agpaitic, nepheline syenite solidus (at 700°C), at pressures between 3.5 and 5.5 kbar, compatible with magmatic exsolution of these fluids at crustal depths of between 11-18 km. By contrast, fluid-phase equilibria and the shallow slopes of isochores derived from the PVTX modelling of CH4-dominant and related inclusions are indicative of trapping conditions at pressures of 0.5 to 1.8 kbar. The close association of CH4 inclusions with magnetite and late-stage hydrated phases suggests evolution of CH4 during hydration within a reducing environment. This evolution involved subsolidus Fischer-Tropsch reactions of the type CO2 + 4H2 → CH4 + 2H2O, with the water-produced driving hydration reactions which generated magnetite and more H2. Methane production is thus a function of vapour-mineral reactions in the C-H-O system operative during late-stage hydrothermal processes and, in particular, is due to two self-reinforcing reaction types linked through a positive feedback mechanism.